PERJANJIAN CARTER KAPAL NIAGA DALAM PERSPEKTIF HUKUM PERJANJIAN DI INDONESIA - Hendra Djaja (University of Merdeka Malang, 2017)
Law no 17 year 2008 about voyage applies a sabotage principle. This principle is significantly proven that itincreases the use of ship with Indonesian flag on it in all activities in voyage sector in Indonesian law territory,so it reduces the dependence to the ships with foreign flags. This principle does not influence so much to thedynamics of the commerce transportation company need to rent the ships either foreign ships or Indonesianones through the mechanism of the chartering of vessels or charter party, except if the policy of sea toll isreally implemented. Generally there are three kinds of charter party namely voyage charter, time charter andbareboat charter. The contract content of this vessel charter fully obeys the freedom of parties. However,practically in commerce voyage, there are various kinds of charter contracts forming standard charter party(approved documents) that arrange like essential clauses or additional clause that must be understood well bythe parties. This understanding is important because it has an impact for not only the parties tied to charterparty but also their responsibility on the loss of transportation users.Undang Undang Nomor 17 Tahun 2008 tentang Pelayaran menerapkan asas cabotage.Asas ini secara signifikanterbukti meningkatkan penggunaan kapal berbendera Indonesia dalam seluruh aktivitas kegiatan usaha sektorpelayaran di wilayah hukum Indonesia, sehingga mengurangi ketergantungan terhadap kapal berbenderaasing.Asas tersebut tidak terlalu berpengaruh terhadap dinamika kebutuhan perusahaan angkutan niagauntuk menyewa kapal, baik asing maupun sesama kapal niaga Indonesia melalui mekanisme the chartering ofvessels atau charter party, kecuali apabila kebijakan Tol Laut pemerintah sekarang ini betul-betuldiimplementasikan.Secara umum terdapat tiga jenis charter party yaitu voyage charter, time charter danbareboat charter. Isi perjanjian carter kapal ini sepenuhnya tunduk pada kebebasan para pihak. Namun demikiandi dalam praktek pelayaran niaga, dikenal berbagai jenis perjanjian carter yang berbentuk standard charterparty (approved documents) yang mengatur antara lainklausula-klausula esential atauadditional clause danharus dipahami dengan baik oleh para pihak. Pemahaman ini penting karena berdampak tidak saja bagi parapihak yang terikat charter party, tetapi juga terhadap tanggung jawab mereka atas kerugian pihak penggunajasa angkutan.